rezolvati ecuatia [3inmultit(x+ - 2.7)-4.2]:1.5 = 7.2
]
Răspunsuri la întrebare
Răspuns de
6
{3x[x+(-2.7)-4.2]:15}=7.2
[3x(x+6.9-4.2):15]=7.2
[3x(x+2.7):15]=7.2
(3x+2.7x:15)=7.2
(3x+0.18x)=7.2
3,18x=7.2
x=7.2:3.18
x=40
[3x(x+6.9-4.2):15]=7.2
[3x(x+2.7):15]=7.2
(3x+2.7x:15)=7.2
(3x+0.18x)=7.2
3,18x=7.2
x=7.2:3.18
x=40
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Ed. muzicală,
10 ani în urmă
Limba română,
10 ani în urmă